UALGORITMO, a New Instrument of the University of Algarve for Scientific Outreach - José Bragança; Sónia Figueiredo; Carla Alexandra Rego; Filomena dos Reis Conceição; Saúl Neves de Jesus (MDPI AG, 2022)
Researchers at Universities generate and convey the knowledge acquired through communications in specialized (inter)national journals and congresses. An effort to share the scientific achievements with the general public is extremely important. For this purpose, we have launched the UALGORITMO, a journal freely accessible online, written in lay Portuguese language by Researchers of the University of the Algarve, to summarize recent communications published in peer reviewed journals. After submission, the manuscripts are revised by High Schools Students of the Algarve, under the guidance of a schoolteacher, for further simplification of the language and general improvement of the manuscript and figures. The revised manuscripts by the authors are edited and published, with an acknowledgment and a presentation of the reviewers at the end of each article. To maximize the outreach, the articles include a summarized biography of the authors, and links to their research centers and teaching courses. We believe that the UALGORITMO is a valuable instrument to promote scientific literacy and culture amongst all communities.